Market Efficiency: Stock Market Behaviour in Theory and Practice - LeRoy, Stephen F. (Review of Financial Studies, 1998)
In Market Efficiency: Stock Market Behaviour in Theory and Practice, Andrew W. Lo has collected the major papers, both theoretical and empirical, that have defined the development of the theory of efficient capital markets. The first volume has an introduction by the editor and a foreword by Richard Roll. Both are brief—too brief, in my opinion—but excellent. The papers are grouped into five parts. In Volume I, Part I is “Theoretical Foundations.” The included articles are by Black (1986), Fama (1970), Grossman (1976), Grossman and Stiglitz (1980), LeRoy (1973), Lucas (1978), and Samuelson (1965). Part II is “The Random Walk Hypothesis.” The articles are by Cootner (1962), Cowles and Jones (1937), Fama (1965), Fama and Blume (1966), Fama and French (1988), French and Roll (1986), Jegadeesh (1990), Kim, Nelson, and Startz (1991), Lo (1991), Lo and MacKinlay (1988), Osborne (1959), Porterba and Summers (1988), and Richardson (1993). In Volume II, Part I is “Variance Bounds Tests.” Included articles are by Campbell and Shiller (1989), Flavin (1983), Gilles and LeRoy (1991), Grossman and Shiller (1981), Kleidon (1986), LeRoy and Porter (1981), Marsh and Merton (1986), Merton (1987), Michener (1982), Shiller (1981), and West (1988).